Genealogy of the figures of “troubled” childhood and youth in modern Argentina (Tempo e Argumento, 2022)
This article explores the hypothesis of the existence of an intrinsic relationship between the configuration of public problems located in different historical moments in Argentina, and the definition of the attributes of childhood and youth condition, those considered hegemonic and also classified as "problematic”. For this purpose, it revises socio-historical research on childhood and youth regarding the perspectives of relational socio-anthropology of ages and the sociology of public problems. As a result, it presents a genealogy of the most emblematic “figures of childhoods and youths problematics” in Argentina and their hegemonic approach, which has led to public discussions from the end of the 18th century (starting with the first institution aimed to children) to present day. Constructing such a genealogy requires accounting for the social conditions that made possible the emergence of certain figures, the theoretical conceptions and disciplines that organized the discourses at different periods, the actors who intervened at the public debate and the institutional responses that they aroused and gave shape to these institutions. From the figure of the "illegitimate son" in viceregal society to the current figure of the “minor delinquent” or “pibe chorro”, these figures constitute an interpretive framework, an available cultural sediment in which actors inscribe the constructions of each new problem, following them and re signifying them in dialogue with current social processes.
Keywords: “troubled” childhood and youth; social construction of minority; sociology of public problems